Comparative pharmacokinetics of polymyxin B in critically ill elderly patients with extensively drug-resistant gram-negative bacteria infections - Zeng, Juan; Leng, Bing; Guan, Xiaoyan; Jiang, Shuangyan; Xie, Maoyu; Zhu, Wenying; Tang, Yue; Zhang, Lin; Sha, Jing; Wang, Tengfei; Ding, Min; Guo, Nan; et al. (Frontiers in Pharmacology, 2024)
Elderly patients are more prone to develop acute kidney injury during infections and polymyxin B (PMB)-associated nephrotoxicity than young patients. The differential response to PMB between the elderly and young critically ill patients is unknown. To assess PMB exposure in elderly patients compared with young critically ill patients, and to determine the covariates of PMB pharmacokinetics in critically ill patients, seventeen elderly patients (age ≥65 years) and six young critically ill patients (age<65 years) were enrolled. Six to eight blood samples were collected during the 12h intervals after at least six doses of intravenous PMB in each patient. PMB plasma concentrations were quantified by high-performance liquid chromatography-tandem mass spectrometry. The primary outcome was PMB exposure as assessed by the area under the concentration-time curve over 24h at steady state (AUCss, 0-24h). The elderly group had lower total body weight (TBW) and higher Charlson comorbidity scores than young group. Neither AUCss, 0-24h nor normalized AUCss, 0-24h (adjusting AUC for the daily dose in mg/kg of TBW) was significantly different between the elderly group and young group. The half-life time was longer in the elderly patients than in young patients (11.21 vs 6.56 h respectively, P=0.003). Age and TBW were the covariates of half-life time (r=0.415, P=0.049 and r=-0.489, P=0.018, respectively). TBW was the covariate of clearance (r=0.527, P=0.010) and AUCss, 0-24h (r=-0.414, P=0.049). Patients with AUCss, 0-24h ≥100mg•h/L had higher baseline serum creatinine levels and lower TBW than patients with AUCss, 0-24h <50mg•h/L or patients with AUCss, 0- 24h 50-100mg•h/L. The PMB exposures were comparable in elderly and young critically ill patients.High baseline serum creatinine levels and low TBW was associated with PMB overdose. Trial registration ChiCTR2300073896 retrospectively registered on